2008
DOI: 10.1002/ejoc.200800252
|View full text |Cite
|
Sign up to set email alerts
|

Superacid‐Catalyzed Dimerization/Cyclization of Isopropenyl‐PAHs – Novel Pathways to PAH Dimers, Phenalenes and Their Stable Carbocations

Abstract: The isopropenyl derivatives of representative classes of polycyclic aromatic hydrocarbons (PAHs) having four and five fused‐ring systems, namely pyrene, chrysene, benzo[c]phenanthrene (BcPh), dibenzo[a,c]anthracene (benzo[f]tetraphene) and perylene, were synthesized by Wittig olefination from the corresponding acetyl‐PAHs. Under the influence of triflic acid (TfOH), the isopropenyl derivatives were converted to novel PAH dimers and/or phenalenes in a simple one‐pot procedure. A plausible mechanism for this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Brule et al [59] reported an example of the interpretation of the charge distribution from NMR chemical shifts in several benzylic carbocations. We take 3-isopropenylperylene as an example.…”
Section: Other Arenium Ionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Brule et al [59] reported an example of the interpretation of the charge distribution from NMR chemical shifts in several benzylic carbocations. We take 3-isopropenylperylene as an example.…”
Section: Other Arenium Ionsmentioning
confidence: 98%
“…(8). 13 C NMR-derived charge delocalization modes in the carbocation resulting from the protonation of 3-isopropenylperylene [59]. The circles are related to the magnitude of 13 C. 9 The Gauge invariant atomic orbital (GIAO) method [57; 58] allows the obtention of gauge invariant wavefunctions from which NMR chemical shifts can be calculated and interpreted in terms of charge delocalization modes as in references [52][53][54][55][56].…”
Section: Other Arenium Ionsmentioning
confidence: 99%
“…The isopropenyl derivatives of a range of polycyclic aromatic hydrocarbons (PAHs) having four and five-membered fused ring systems were prepared by Wittig olefination of the corresponding acetyl PAHs. 25 In the presence of triflic acid these derivatives converted to PAH dimers 37 and/or phenalenes 38 (shown in Scheme 10 for the isoprenyl derivative of phenanthrene). The mechanism of formation of dimers and subsequently phenalenes was suggested to proceed via several carbocation intermediates.…”
Section: Reactions Involving Carbocationsmentioning
confidence: 99%